STAT1‐ and NFAT‐independent amplification of purinoceptor function integrates cellular senescence with interleukin‐6 production in preadipocytes. (23rd November 2022) - Majeed, Yasser; Madani, Aisha Y.; Altamimi, Ahmed I.; Courjaret, Raphael; Vakayil, Muneera; Fountain, Samuel J.; Machaca, Khaled; Mazloum, Nayef A.
Abstract: Background and Purpose: Senescent preadipocytes promote adipose tissue dysfunction by secreting pro‐inflammatory factors, although little is known about the mechanisms regulating their production. We investigated if up‐regulated purinoceptor function sensitizes senescent preadipocytes to cognate agonists and how such sensitization regulates inflammation. Experimental Approach: Etoposide was used to trigger senescence in 3T3‐L1 preadipocytes. CRISPR/Cas9 technology or pharmacology allowed studies of transcription factor function. Fura‐2 imaging was used for calcium measurements. Interleukin‐6 levels were quantified using quantitative PCR and ELISA. Specific agonists and antagonists supported studies of purinoceptor coupling to interleukin‐6 production. Experiments in MS1 VEGF angiosarcoma cells and adipose tissue samples from obese mice complemented preadipocyte experiments. Key Results: DNA damage‐induced senescence up‐regulated purinoceptor expression levels in preadipocytes and MS1 VEGF angiosarcoma cells. ATP‐evoked Ca 2+ release was potentiated in senescent preadipocytes. ATP enhanced interleukin‐6 production, an effect mimicked by ADP but not UTP, in a calcium‐independent manner. Senescence‐associated up‐regulation and activation of the adenosine A3 receptor also enhanced interleukin‐6 production. However, nucleotide hydrolysis was not essential because exposure to ATPγS also enhanced interleukin‐6 secretion. Pharmacological experiments suggested coupling of P2X ion channels and P2Y12 –P2Y13 receptors to downstream interleukin‐6 production. Interleukin‐6 signalling exacerbated inflammation during senescence and compromised adipogenesis. Conclusions and Implications: We report a previously uncharacterized link between cellular senescence and purinergic signalling in preadipocytes and endothelial cancer cells, raising the possibility that up‐regulated purinoceptors play key modulatory roles in senescence‐associated conditions like obesity and cancer. There is potential for exploitation of specific purinoceptor antagonists as therapeutics in inflammatory disorders.